2001
DOI: 10.1247/csf.26.593
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cytokinesis Research. Determination of Division Plane and Organization of Contractile Ring in Tetrahymena.

Abstract: ABSTRACT. In the molecular mechanism of division plane determination and contractile ring formation, Tetrahymena 85kDa protein (p85) is localized to the presumptive division plane before the formation of the contractile ring. p85 directly interacts with Tetrahymena calmodulin (CaM) in a Ca 2+ -dependent manner, and p85 and CaM colocalize in the division furrow. A Ca 2+ /CaM inhibitor N-(6-Aminohexyl)-5-chloro-1-naphthalenesulfonamide HCl (W7) inhibits the direct interaction between p85 and Ca 2+ /CaM. W7 also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…cdaA-1 is perhaps the most extensively studied mutation of this set, with 20 publications (15,17,18,19,20,48,49,52,54,56,59,60,81,83,86,87,119,120,121,156). cdaA-1 is a 100%-penetrant temperature-sensitive mutation, located on chromosome 4R (15; E. Hamilton, personal communication), that at 39°C permits an OP to be initiated and develop at its normal position but prevents all other known structural (49) (Fig.…”
Section: The Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…cdaA-1 is perhaps the most extensively studied mutation of this set, with 20 publications (15,17,18,19,20,48,49,52,54,56,59,60,81,83,86,87,119,120,121,156). cdaA-1 is a 100%-penetrant temperature-sensitive mutation, located on chromosome 4R (15; E. Hamilton, personal communication), that at 39°C permits an OP to be initiated and develop at its normal position but prevents all other known structural (49) (Fig.…”
Section: The Mutationsmentioning
confidence: 99%
“…At a restrictive temperature, these couplets did not form at their normal sites just posterior to the fission zone, and p85 was not localized at these sites (121). These authors presumed that there is a causal connection between the localization of p85 and the capacity to form a fission zone, a line of analysis that was pursued further by the Numata group (60,119). One problem with this analysis is that both apical basal-body couplets and p85 are absent between the fourth ciliary row to the right and the first row to the left of the OA When the cDNA that coded for p85 was cloned and sequenced, it was found that "there was no difference in the predicted amino acid sequences of wild-type and cdaA1 p85" (59).…”
Section: The Mutationsmentioning
confidence: 99%
“…Contractile ring filaments are associated with myosin II and numerous other actin‐binding proteins. An actin contractile ring has been identified in dividing Tetrahymena (Gonda et al 1999; Hirono et al 1987; Numata and Gonda 2001), and several actin‐binding proteins including profilin (Edamatsu et al 1992) and the F‐actin binding protein, p71, (Watanabe et al 1998) have been localized to the division furrow. Calmodulin and the novel Tetrahymena protein p85 are proposed regulators of cytokinesis in Tetrahymena (Gonda et al 1999).…”
mentioning
confidence: 99%
“…A number of proteins dealing with Ca 2+ signaling are also assembled at the pore. In Tetrahymena, Ca 2+ -binding proteins include calmodulin (Numata & Gonda, 2001) and centrin, Cen4 (Stemm-Wolf et al, 2005). In Paramecium, this is complemented by CRCs whose overall sequence is related to InsP 3 R and RyRs, including PtCRC-VI-2 and PtCRC-VI-3 (Ladenburger & Plattner, 2011).…”
Section: Pore Components: Ca 2+ -Binding Proteins Tubulins Myosin Amentioning
confidence: 99%
“…Changes in the local concentration of Ca 2+ could play a role, possibly in conjunction with calmodulin and centrin. In fact, calmodulin and centrin, isoform Cen4, occur at the pore in Tetrahymena (Numata & Gonda, 2001) and in Paramecium (Stemm- Wolf et al, 2005), together with g-tubulin. Nevertheless, it may be mere coincidence that all these components are also found in metazoan centrioles (Dobbelaere et al, 2008;Hodges et al, 2010) and in functional counterparts, the basal bodies of ciliates (Gogendeau et al, 2008;Momayezi et al, 1986;Shang et al, 2002).…”
Section: Site Of De Novo Formation Of Cvcs In Paramecium and Its Molementioning
confidence: 99%